“What’s in a Name?”: H.D.’s Re-Vision of Shakespeare - Claire Conilleau (Transatlantica)
H.D. is both a familiar figure of the Imagist movement fashioned by Ezra Pound and an elusive author of “high modernism.” Primarily known as a poet, H.D. wrote a lot of posthumously published autobiographical prose to disentangle herself from the enshrouding influence of Imagism and the “war trauma.” Shakespeare is a powerful ally for he embodies the intersection between the personal and the literary, the real and the fictional. His plays underwrite H.D.’s autobiographical prose in relation to family, history and identity. H.D. excavates Shakespeare and his plays to reinscribe them in a new body of work – a strategy which enables her to engage with the male literary history and re-vise it by establishing a familial rather than adversarial relation to tradition. This article envisions the complex interactions between Shakespeare’s text and H.D.’s prose as the cornerstone of her positioning as woman writer in the economy of literary creation. It explores the creative diversions and reappropriations of Shakespeare’s plays that H.D. resorts to, especially her play with onomastics, the evocations and inscriptions of the Bard and his plays in the body of her works as well as a lesser known text, By Avon River, whose theme is Shakespeare himself.